Nationwide survey on ICU visiting policies in Mainland of China: Current practices and perspectives - Yanxia Huang; Mei Meng; Xiaojun Pan; Sheng Zhang; Lidi Zhang; Jiao Liu; Dechang Chen (Journal of Intensive Medicine, 2025)
Background: Family presence is essential in reducing delirium and promoting early recovery of patients in the intensive care unit (ICU). This study was conducted through a questionnaire survey to examine the current visitation policies of ICUs in China and explore flexible visitation options. Methods: Two versions of independently developed questionnaire, informed by relevant literature, was distributed in two versions: a medical staff questionnaire and a family questionnaire. The survey was administered online and conducted anonymously, with participants completing it after scanning a two-dimensional bar code. Data were collected from January 2020 to June 2020. We accessed the difference between the two groups were compared and the association between factors associated with family satisfaction were assessed. Results: A total of 1200 hospitals across 30 provinces participated, yielding 16,359 valid responses (13,483 from medical staff and 2876 from family members). Currently, 90.5 % of the ICUs allow once-daily visitation, whereas only 1.2 % permit unrestricted visitation. Family care was allowed in 15.0 % of the ICUs at the end of the patient's life, and 30.3 % allowed flexible visitation for rehabilitation exercises. Among medical staff, 73.9 % of doctors and 58.7 % of nurses supported flexible visitation when rehabilitation exercises are needed. In addition, 73.3 % of family members were willing to help with rehabilitation exercises, and 77.3 % were satisfied with the existing visitation policies. Conclusions: Most ICUs in mainland of China enforce restrictive visitation policies, most medical staff and family members accept. Moreover, flexible visitation policies for rehabilitation purposes may be increasingly acceptable in the future.